AN ANALYSIS OF INFLECTIONAL AFFIXES IN ARIANA GRANDE’S SONG LYRICS - Fitri Sondakh; Sanerita Tresnawati Olii; Paula Rombepajung (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This research aimed to analyze the types of inflectional affixes in Ariana Grande’s song lyrics. The method employed in this research was the descriptive qualitative method. The data of this research were in the form of words from Ariana Grande’s song lyrics which consist of inflectional suffixes. The source of the data was five of Ariana Grande’s songs entitled ‘My Everything’, ‘One Last Time’, ‘Just a Little Bit of Your Heart’, ‘Point of View’, and ‘Almost is Never Enough’. The data were collected through listening to the songs, reading the lyrics, and taking notes of the words which consist of inflectional affixes. The results showed that there are seven types of inflectional affixes found in the song lyrics, which were noun plural, present participle, comparative, present third-person singular, past participle, past tense, and noun singular possessive. The type of inflectional affix which found the most is the present participle which occurs 18 times. Then, nine plurals with a total of 11 occurrences. After that, the following noun plural was past tense which was found in 6 different lyrics. Next was present third-person singular with 3 occurrences. Then, the fifth position was comparative which is found in 2 lyrics. Finally, the least used type of inflectional affixes was past participle and noun singular possessive which only appears one time each